The Effect of Free Nutritious Meals (MBG) on Economic Growth of South Sumatera - Megry Fatra Humbara; Abdul Basyith; Fitriya Fitriya (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
The Free Nutritious Meals (MBG) program is one of Indonesia's flagship government initiatives aimed at improving nutritional status, strengthening human capital, and promoting inclusive economic development. Beyond its social objectives, the program is expected to stimulate regional economic activity through increased demand for locally produced food commodities, employment creation, and multiplier effects across agricultural and food supply chains. However, empirical evidence regarding its contribution to regional economic growth remains limited. This study examines the impact of the MBG program on economic growth in South Sumatra Province by comparing regional economic performance before (2023–2024) and after (2025) the implementation of the program. A quantitative comparative research design was employed using a before-and-after approach. The study focuses on six districts and municipalities representing the highest and lowest Human Development Index (HDI) categories. Data were obtained from official publications of the Central Statistics Agency (BPS) of South Sumatra Province. The analysis applies descriptive statistics, paired-samples t-tests, and simple linear regression to evaluate the program's economic impact. The findings reveal a statistically significant increase in regional economic growth following the implementation of the MBG program. The regression results further indicate that the program exerts a positive and significant influence on economic growth, suggesting that government expenditure on nutrition programs functions as an effective fiscal stimulus capable of generating local economic multiplier effects. Moreover, the analysis demonstrates that the program produces stronger economic impacts in regions with lower HDI, implying that less-developed areas derive greater benefits from public investments in nutrition and human capital. These findings support Keynesian fiscal theory and human capital theory, highlighting the dual role of nutrition programs as instruments for improving social welfare and promoting regional economic development. The study recommends prioritizing MBG implementation in disadvantaged regions while strengthening local agricultural supply chains to maximize its long-term economic benefits.